Legal regulation of public-private partnership - Kurmanov, A.A.; Kurmanova, S.B. (Bulletin of the Karaganda University “Law Series”, 2023)
The development of public infrastructure requires the use of various forms of interaction between private business and the state. Among such facilities is a public-private partnership. Public-private partnership gives positive results, such as attracting investments, saving budget resources, stimulating competition and entrepreneurial activity, thanks to its successful application in many developed countries, its regulation has found its place in the country’s regulatory legal acts. Thus, according to Kazakh Public-Private Partnership Center, 786 public-private partnership agreements have been concluded in the field of education alone until June 1, 2020. This represents 56 percent of all contracts concluded. The purpose of the article is to analyze the legal aspects of regulation of public-private partnership. In the article, the author comprehensively explores, formulates and reveals the content of the principles of legal regulation of public-private partnership. On this issue, the existing positions in the scientific literature will be analyzed; their new ideas on this issue will be considered. The normative acts of international organizations, as well as the EAEU countries, economies of which are closely interconnected, are analyzed. It is proved that such principles as the initial principles, provisions expressing the essence of the institution of public-private partnership should be legislatively fixed to ensure uniformity of legal regulation. As a result of the work carried out, the mechanisms of legal regulation will be disclosed, compared with the experience of other countries, the advantages and disadvantages will be discussed.